2013
DOI: 10.1007/s11414-013-9359-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enablers to Integrating Mental Health into Primary Care: A Policy Analysis

Abstract: Integrating care for physical health and behavioural health (mental health and addictions) has been a longstanding challenge, although research supports the clinical and cost effectiveness of integrated care for many clients. In one such model, primary care (PC) physicians work with specialist physicians and non-physician providers (NPPs) to provide mental health and addictions care in PC settings. This Ontario, Canada-focused policy analysis draws on research evidence to examine potential barriers and enabler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 65 publications
1
31
0
1
Order By: Relevance
“…Providers are able to collaborate on cases and coordinate treatment plans in a routine fashion. 8,9 It is unknown, however, whether integrated care teams actually serve as a buffer to the risks of burnout in physicians. In this study, we explored whether higher levels of integrated care practice are associated with lower rates of burnout and depersonalization of primary care physicians.…”
mentioning
confidence: 99%
“…Providers are able to collaborate on cases and coordinate treatment plans in a routine fashion. 8,9 It is unknown, however, whether integrated care teams actually serve as a buffer to the risks of burnout in physicians. In this study, we explored whether higher levels of integrated care practice are associated with lower rates of burnout and depersonalization of primary care physicians.…”
mentioning
confidence: 99%
“…Given that the bulk of literature on primary care incentives focuses on single-provider models of care, future research is needed to generate knowledge about incentive models relevant for interprofessional primary care settings. Realigning incentive systems for interprofessional primary care contexts is necessary if optimal prevention and management of CMDs is going to be achieved in Canada (Dewa et al 2001; Durbin et al 2016; Mulvale et al 2008; Rush et al 2013; Steele et al 2013). Understanding incentives and disincentives influencing care is essential in order to achieve greater integration and capacity for care (Ashcroft et al 2014; Craven and Bland 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of these models have demonstrated increased patient and provider satisfaction as well as significant reductions in treatment delays and costs. [3][4][5] collaborative care…”
Section: Introductionmentioning
confidence: 99%